QUANTITATIVE COMPUTED TOMOGRAPHY DENSITOMETRY IN EMPHYSEMA AND ITS RELATIONSHIP WITH QUALITATIVE VISUAL SCORING AND PULMONARY FUNCTION TESTS - Nikolova, Sonja (Institute of Knowledge Management, 2023)
Emphysema as common and rather pathological entity is classified among the chronic obstructive pulmonary diseases (COPD) and defined as abnormal and irreparable increase in size of the airspaces located caudally to the terminal bronchioles that may go along with alveolar wall destruction but no evident fibrosis. Not only is CT being used as a regular diagnostic tool in the detection of emphysema, but in recent years offers a phenotypic classification and quantification of lung abnormalities that assists the clinical characteristics of the patients involved. The aim of this study was to demonstrate significant correlation between quantitative CT densitometry on one side, and the visually assessed CT subtypes as well as the function lung tests on the other side in patients with emphysema. In total of 10 patients diagnosed with emphysema, 8 male and 2 female, with the mean age of 61. 3± 14. 84 , who underwent a CT exam, a quantitative CT densitometry was calculated and compared to 5 visually acquired CT subtypes using the Fleischner Society classification: normal, bronchial disease and centrilobular emphysema ( trace, mild and advanced destructive). A correlation was also made with the pulmonary function tests (FEV1 and FEV1/ FVC ratio). There is a strong positive correlation which is statistically significant for p< 0.5 for the parameters of quantitative assessment with -950HU calculated on the CT densitometry and the CT visual scoring, as well as statistically significant and strong negative correlation between the pulmonary function tests, FEV1 and FEV1/ FVC ratio, respectively. The pulmonary function tests, according to the Global Initiative for Chronic Obstructive Lung Disease (GOLD), revealed that 30% of our patients had mild, severe and very severe obstructive defect respectively, where only 10% had moderate obstructive defect. Quantitative CT densitometry, already being a non- invasive study, also plays a major role in detecting, clearly depicting and quantifying lung zones involved with emphysema and provides rapid evaluation of the severity of emphysema. Quantitative CT densitometry with its accurate illustration of the extent and distribution of lung abnormalities in emphysema may aid the selection of patients who are suitable for lung reduction surgery
Keywords: emphysema; quantitative computed tomography (QCT); densitometry; visual score; pulmonary function tests (PFT)